Analysis of 17α-ethinylestradiol and bisphenol A adsorption on anthracite surfaces by site energy distribution. (February 2019) - He, Jing; Guo, Jinsong; Zhou, Qiuhong; Yang, Jixiang; Fang, Fang; Huang, Yang
Abstract: 17α-Ethinylestradiol (EE2) and bisphenol A (BPA) are highly toxic and widely detected endocrine-disrupting compounds (EDCs) throughout the world in surface waters. Adsorption is an effective way to remove EE2 and BPA from water. However, it is difficult to clearly explain the mechanism of adsorption theoretically only through classic adsorption models. In order to insight into the adsorption of EE2 and BPA, site energy distribution (SED) theory was introduced to investigate the adsorption of EE2 and BPA on heterogeneous surfaces. EE2 and BPA were adsorbed on un-anthracite (unmodified anthracite) and 4K anthracite (4 mol L −1 KOH-modified anthracite) in single- and bi-component systems under various temperatures and pHs. The results suggested that EE2 and BPA molecules first occupied the high-energy adsorption sites and then spread to low-energy adsorption sites. There were more high-energy sites on 4K anthracite, resulting in a higher adsorption capability for EE2 and BPA. Besides, increasing temperature and acidic environment were conducive to the EE2 and BPA adsorption. SED analyses indicated that, in neutral solutions, π-π electron donor-acceptor (EDA) interaction might be the primary mechanism for BPA adsorption, while ligand exchange, hydrogen bonds, and π-π EDA interaction might simultaneously work in the adsorption of EE2. It was possible that EE2 molecule was near perpendicular to surface, while BPA molecule was parallel to surface, resulting in the higher adsorption capacities of EE2. However, compared with EE2, BPA had outstanding competitive advantages in bi-component system because of the stronger π-π EDA interaction between BPA and anthracite. Graphical abstract: Highlights: Novel insight into the adsorption of EE2 and BPA on anthracite surface was given. Site energy distribution was used to investigate the adsorption of EE2 and BPA. More high-energy sites on 4K anthracite resulted in a higher adsorption capability. BPA had competitive advantages in high-energy area in bi-component system.